Implementation of Teacher Certification in Improving Teacher Performance in 1 Rambutan Junior High School - Syarifuddin; Harapan, Edi; Wardiah, Dessy (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2021)
This study aims to identify and describe the implementation of teacher certification in improving teacher performance at SMP Negeri 1 Rambutan. With a qualitative descriptive research method, the use of qualitative descriptive research design in this study is intended to describe and analyze the implementation of teacher certification, especially to obtain an overview of the relationship between teacher certification and teacher performance. Data collection techniques in this study through interviews, observation, documentation and triangulation. The results obtained from the research Almost all teachers at SMP Negeri 1 Rambutan have an S1 diploma, it is estimated that 90% of PNS teachers in this school have been certified. Of course this affects both the school and the school environment. With education that meets the standards that teachers have in accordance with their scientific fields, it will certainly have a major influence on the learning process in this school.